Insights into the bacterial fraction of sediments from the South China Sea: physiological, chemotaxonomic, and genomic characterization of seven novel members of the Bacillaceae family - Ge, Shu-Tong; Cheng, Hong; Zhong, Ying-Wen; Tang, Jia-Ling; Huang, Xin-Yue; Wei, Bin; Wu, Yue-Hong; Wang, Chun-Sheng (Frontiers in Microbiology, 2025)
The family Bacillaceae is phenotypically and phylogenetically heterogeneous group of bacteria, which has vast metabolic capability in carbohydrates degradation and secondary metabolite production. Deep marine sediments harbor highly diverse microorganisms, playing important roles in ecosystem. Here, we investigated the cultivable fraction of bacteria associated with the sediments of South China Sea (n = 152). After obtaining candidate novel strains, the morphological and physiological characteristics analysis were conducted for polyphasic taxonomy. Additionally, the whole genome sequencing, annotation and comparative genomic analysis were performed for their specific metabolic characteristics. As a result, seven novel members of the family Bacillaceae have been established: Pseudalkalibacillus nanhaiensis sp. nov. (Strain SCS-8T), Paraperibacillus marinus sp. nov. (Strain SCS-26T), Neobacillus oceani sp. nov. (Strain SCS-31T), Paraperibacillus esterisolvens sp. nov. (Strain SCS-37T), Nanhaiella sioensis gen. nov., sp. nov. (Strain SCS-151T), Rossellomorea sedimentorum sp. nov. (Strain SCS-153AT) and Peribacillus sedimenti sp. nov. (Strain SCS-155T). These novel srains display smaller genome sizes and distinctive characteristics. The annotation of Cluster of Orthologous Genes (COG) revealed a higher specific gene abundance in these strains in the carbohydrate transport and metabolism (COG-G), secondary metabolites processes (COG-Q), and the cell membrane-related functions (COG-M). These Bacillaceae species isolated from sediment have different capability to degrade carbohydrates and produce biosynthetic products compared to other reference strains, revealing that they have unique adaptation strategies to the deep marine sediments.